Novel sulfonated poly(ether ether ketone)/triphenylamine hybrid membrane for vanadium redox flow battery applications. Issue 7 (29th January 2019) - Quan, Yizhou; Wang, Gang; Li, Anfeng; Wei, Xiaoyan; Li, Feng; Zhang, Jie; Chen, Jinwei; Wang, Ruilin
Abstract : The novel TPAM hybrid membrane exhibited both lower vanadium permeability and higher proton conductivity than pristine SPEEK membrane. Abstract : A novel sulfonated poly(ether ether ketone)/triphenylamine hybrid membrane with various triphenylamine loadings (1%, 2% and 5%) has been successfully fabricated. Optimum triphenylamine loading was confirmed by exploring the physicochemical properties and morphology of different membranes. The hybrid membrane exhibited lower vanadium permeability than pristine SPEEK membranes due to the acid–base interaction between amine groups and sulfonated groups. Introduction of triphenylamine also improved the proton conductivity because the nitrogen atom of triphenylamine can be protonated and contribute to the proton transfer. As the result, the hybrid membrane demonstrated higher ion selectivity compared with SPEEK and Nafion115 membranes. The VRFB single cell with SPEEK/TPAM-1% membrane showed better performance compared to a Nafion115 membrane at the current density of 60 mA cm −2 . The SPEEK/TPAM hybrid membrane has great potential for VRFB application.